Latent variable modeling and its implications for institutional review board review: variables that delay the reviewing process - Tzeng, Dong-Sheng; Wu, Yi-Chang; Hsu, Jane-Yi (BMC medical ethics, 2015)
Background To investigate the factors related to approval after review by an Institutional Review Board (IRB), the structure equation model was used to analyze the latent variables ‘investigators’, ‘vulnerability’ and ‘review process’ for 221 proposals submitted to our IRB. Methods The vulnerability factor included vulnerable cases, and studies that involved drug tests and genetic analyses. The principal investigator (PI) factor included the license level of the PI and whether they belonged to our institution. The review factor included administration time, total review time, and revision frequency. The revision frequency and total review time influenced the efficiency of review. Results The latent variable of reviewing was the most important factor mediating the PIs and vulnerability to IRB review approval. The local PIs moderated with genetic study and revision frequency had an impact on the review process and mediated non-approval. Conclusions Better guidance of the investigators and reviewers might improve the efficiency with which IRBs function.